2016
DOI: 10.1002/lary.26134
|View full text |Cite
|
Sign up to set email alerts
|

Review of videolaryngoscopy pharyngeal wall injuries

Abstract: Our data suggests that using video-assisted laryngoscopy for intubation puts a patient at significantly greater risk for injury compared to direct laryngoscopy. Laryngoscope, 2016 127:349-353, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 27 publications
4
45
0
Order By: Relevance
“…Even the manufacturer of the GlideScope videolaryngoscope advocates the use of a special tracheal tube, the GlideRite ® tracheal tube (Highlands Ranch, CO), to address this troublesome (17). It has been shown that compared with the standard tracheal tube, the GlideRite ® tracheal tube significantly improves intubation with the GlideScope videolaryngoscope, as measured by decreased time for tube insertion and increased ease of tube insertion assessed by a visual analog scale (65). When videolaryngoscope with a channelled blade is used, obtaining an optimal view of the larynx is required because this can ensure that the tracheal tube is directed correctly through the guide channel towards the glottis.…”
Section: How To Get the Best Out Of Videolaryngoscopymentioning
confidence: 99%
See 4 more Smart Citations
“…Even the manufacturer of the GlideScope videolaryngoscope advocates the use of a special tracheal tube, the GlideRite ® tracheal tube (Highlands Ranch, CO), to address this troublesome (17). It has been shown that compared with the standard tracheal tube, the GlideRite ® tracheal tube significantly improves intubation with the GlideScope videolaryngoscope, as measured by decreased time for tube insertion and increased ease of tube insertion assessed by a visual analog scale (65). When videolaryngoscope with a channelled blade is used, obtaining an optimal view of the larynx is required because this can ensure that the tracheal tube is directed correctly through the guide channel towards the glottis.…”
Section: How To Get the Best Out Of Videolaryngoscopymentioning
confidence: 99%
“…Minor complications included lip or gum lacerations (n=13); more serious complications (n=6) are vocal cord trauma, tracheal injury, trauma to the hypopharynx, tonsillar perforation and two dental injuries (39). Even Greer et al's review of airway injuries in anesthesia records of the Madigan Army Medical Center shows that the rate of the upper airway injuries associated with videolaryngoscopy is significantly higher compared to direct laryngoscopy, suggesting that inherent design of videolaryngoscopy may contribute to the potential for upper airway injuries (65).…”
Section: How To Get the Best Out Of Videolaryngoscopymentioning
confidence: 99%
See 3 more Smart Citations